A comparison of secondary prevention practice in poststroke and coronary heart disease patients. (August 2016) - Vaněk, J.; Mayer, O.; Seidlerová, J.; Bruthans, J.; Kielbergerová, L.; Wohlfahrt, P.; Krajčoviechová, A.; Filipovský, J.; Cífková, R.
Abstract: Objectives: It is evident that patients with atherosclerotic vascular disease (AVD) benefit from appropriate secondary prevention. In clinical reality, the secondary prevention in AVD patients other than those with coronary heart disease (CHD) is often overlooked. Therefore, we compared the adherence to secondary prevention principles between poststroke and CHD patients. Study design: Descriptive (cross-sectional) study with prospective mortality follow-up. Methods: We examined 1729 chronic patients with AVD (mean age 65.9 (±SD 9.6) years), 964 with CHD, and 765 poststroke (pooled data of Czech samples of EUROASPIRE III, IV, and the ESH stroke survey). The interview was performed 6–36 months after the coronary event/revascularization or the first ischemic stroke, while the mortality follow-up 5 years after this interview. Results: Poststroke patients had a significantly higher risk of persistent smoking, blood pressure ≥140/90 mmHg and LDL ≥2.5 mmol/L than CHD patients [odds ratios adjusted for age, gender and survey were 1.63 (95% CI: 1.13–2.33), 1.38 (95% CI: 1.13–1.69) and 2.26 (95% CI: 1.84–2.78), respectively]. In contrast, poststroke patients showed a lower risk of inappropriate glucose control and hypertriglyceridemia [0.66 (95%CI: 0.54–0.82) and 0.74 (95%CI: 0.61–0.91), respectively]. The prescription rates of antiplatelets/anticoagulants, antihypertensives and statins were also significantly lower in poststroke than in CHD patients (89.4 vs 93.7, 85.9 vs 97.5, and 57.7 vs 89.8, respectively). Mortality analysis was performed in a subsample of 815 subjects interviewed in 2006/07. The 5-year all-cause mortality rates were 25.8% and 13.3% in poststroke and coronary patients, respectively ( P = 0.0023); the hazard ratio for stroke adjusted for major risk factors was 1.85 (95% CI: 1.31–2.63). Conclusions: Compared to CHD patients, poststroke patients are strongly handicapped in terms of poor adherence to secondary prevention target, prescription of basic pharmacotherapies and mortality risk. Highlights: Poststroke patients had higher risk of persistent smoking, raised blood pressure and increased LDL than coronary patients. The prescription rate of basic pharmacotherapies (such as antiplatelets, statins, etc) is also substandard in post-stroke patients. 5-year all-cause and cardiovascular mortality rates are substantially higher in post-stroke patients than in coronary patients, even if adjusted for potential covariates.